Chemical control of rough-leaved dogwood - Brunkow, Glenn Edward (Kansas State University, 2009)
Rough-leaved dogwood (Cornus Drummondii Meyer) is one of the most invasive woody plants in rangeland of Kansas. Reduced prescribed burning due to drought and urban encroachment probably has contributed to its spread. Herbicides are commonly recommended for control of rough-leaved dogwood, but minimal data exists for recommendation development. Ten herbicide treatments were applied in June during late flowering at two locations in northeast Kansas in 2005 and 2006. Each treatment was replicated three times in a randomized complete block design with individual plot sizes of 3 x 3 m. Herbicides were applied with hand sprayers in 1017 L/ha solution. Visual evaluations of defoliation were made about 1 and 12 months after treatment (MAT) and mortality was estimated about 1 year after treatment (YAT). Defoliation 1 MAT varied among herbicides with significant location by year and herbicide by year interactions. Treatments providing greater than 70% defoliation 12 MAT both years were triclopyr + 2,4-D (1.12 + 1.06 kg ae/ha), triclopyr + fluroxypyr (1.83 + 0.61 kg ae/ha), picloram + fluroxypyr (0.41 + 0.41 and 0.82 + 0.82 kg ae/ha), and picloram + 2,4-D + triclopyr (0.66 + 2.44 + 2.44 kg ae/ha). Rough-leaved dogwood is difficult to control with a single herbicide application, but treatments exist that will substantially reduce stands. Tebuthiuron pellets (Spike 20P) are another control measure recommended for rough-leaved dogwood. Treatments of 4.4 kg ai/ha (3/4 oz per 100 square feet) tebuthiuron pellets were applied in December 2004. A visual estimate of control indicated tebuthiuron reduced dogwood cover by 65% compared to a 3% decrease on untreated plots. Dogwood density was reduced by 2.2 stems/m2 (P<0.08). Total woody plant cover increased on untreated plots by 6.2 percentage units, but was decreased by 20.9 percentage units on tebuthiuron treated plots. Other woody plants decreased in both treated and untreated plots. Shading by a large elm tree likely caused variation between replications including increases in cover and density of rough-leaved dogwood on treated plots. Tebuthiuron is a photosynthetic inhibitor that often is not effective on shaded plants. Tebuthiuron pellets applied at 4.4 kg ai/ha was an effective control option for unshaded rough-leaved dogwood.
Keywords: Rough-Leaved Dogwood; Invasive Brush; Chemical Brush Control; Invasive Range Species; Agriculture, Agronomy (0285); Agriculture, Range Management (0777)